Quality of Internal Service, Job Satisfaction and Employment Commitment to Employee Performance Mediated By Employee Welfare at the Bureau of Planning and Administration of the Criminal Reservation Agency - Kumba Digdowiseiso (Institute of Computer Science (IOCS), 2021)
This research was conducted with the aim of knowing and analyzing the influence of internal service quality, job satisfaction and commitment to employee performance which will be mediated by employee welfare. Primary data derived from questionnaires will be used in this study and contain opinions from respondents regarding the quality of internal services, job satisfaction and work commitment to employee performance which will be mediated by employee welfare in the Planning and Administration Bureau of the National Police Criminal Investigation Agency. The use of saturated sampling as a sampling method to get 54 samples. SEM Amos using SEM Amos 22 serves as an analytical method. This research then shows the results in the form of a positive influence of service quality, job satisfaction, and work commitment to employee performance and is significant. Then employee welfare does not have a positive and significant effect on employee performance. Finally, the study found that service quality, job satisfaction and work commitment have a positive and significant influence on employees which is mediated by employee welfare.